School, parents, and financial literacy shape future financial behavior - Antonia Grohmann; Lukas Menkhoff (DIW Economic Bulletin, 2015)
Why do some people make better financial decisions than others do? The level of financial literacy plays an important role: Quality schooling that also deals with financial issues likewise leads to better financial decisions. However, many studies neglect how parenting also influences financial behavior. This report shows that parents also have an indirect effect on the financial literacy of their adult children; in general, specific financial training actually has less of an effect on financial behavior.
Keywords: D14; G11; I20; 330; Financial Literacy; Financial Education; Financial Behaviour